Laura Anna Macor: Die Bestimmung Des menschen (1748-1800): eine Begriffsgeschichte. Fromman Holzboog, 2013, 432 pp. - MACHADO, Lucas Nascimento (Faculdade de Filosofia e Ciências, 2017)
Laura Anna Macor’s Die Bestimmung des Menschen (1748-1800): Eine Begriffsgeschichte is atestament of an enormous philological, historical and philosophical work, one that was no doubt necessary to deal with the amplitude and complexity of the concept it discusses. As Macor herself notes at the beginning of the book, while being maybe one of the fundamental ideas of German’s late Enlightenment, the concept of the “Bestimmung des Menschen” (which could be translated as “the destination of man”, but, due to the untranslatable plurality of meanings of the word, we shall use here without translation) has still had very little research done on it, if compared to other central ideas of that branch of Enlightenment (p. 26).